Explore Related Concepts

Algebraic Identities

Algebraic Identity Definition:

An Identity is an equality which is true for every value of the variable in it.

Example:  ( x+1 ) ( x+2 )   =    x+ 2x + x + 2
                                        =   x+ 3x + 2
         For any value of x LHS is equal to RHS,which shows the appearance of  identity here.
        Some of the identity helpful for solving the problems are given below:
  • (a + b )2 = a2 + 2ab + b2
  • (a - b )2 = a2 -2ab + b2
  • (a + b ) ( a - b ) = a2 - b2
Proof of Identity

                ( a + b)2
                 Step 1: expand the term        =  ( a + b) ( a + b)
                 Step 2: factories                 =  a ( a + b) + b ( a + b)
                 Step 3: simplify =  a+ ab + ba + b2
                 Step 4: add the common term  =  a+ 2ab + b2
                             assign a = 1, b = 2
                            (a + b)2  = a+ 2ab + b2
                            (1 + 2)2  = 12 + 2*1*2 + 22
                                (3)2    =  1 + 4 + 4
                                     9  = 9
                                LHS  = RHS

List of algebraic identity :

The following are some of the important algebraic identities or expression used in class 9th maths

                    1. (a + b)2 = a2 + 2ab + b2

                    2. ( a - b)2 = a2  - 2ab + b2

                    3.  (a + b )  ( a - b ) = a2  - b2

                   4.  ( x + a ) ( x + b ) = x2 + ( a + b) x + ab

                   5.  (x + a ) ( x - b)    = x2 + ( a -b ) x - ab

                   6.  ( x -a ) ( x + b )  = x2 +  ( b - a ) x - ab

                   7.  ( x - a ) ( x - b )  = x2 -  ( a + b ) x + ab

                   8.  ( a + b )3 =  a3 + b3  + 3ab ( a + b )

                   9.  ( a - b )3  = a3  - b3 - 3ab (a - b ) 

                 10.  (x + y + z) = x2 + y2 + z2 + 2xy +2yz + 2xz

                 11.  (x + y - z)2  =  x2 + y2 + z2 + 2xy - 2yz - 2xz

                 12. ( x - y + z)2  = x2 + y2 + z2 - 2xy - 2yz + 2xz

                 13.  (x - y - z)2  = x2  + y2 + z2 - 2xy + 2yz - 2xz

                 14.  x3  + y3 + z3 - 3xyz =  (x + y + z ) ( x2 + y2 + z2 - xy - yz -xz)

                  15. x+ y2  = $\frac{1}{2}$  [( x + y)2 +  ( x - y)2

                  16. ( x + a)  ( x + b)  ( x + c)  =  x+ (a + b + c) x2 +  ( ab + bc + ca ) 
                         x +  abc

                  17.  x3 + y3  =  (x + y) ( x-xy + y)

                  18.  x3  - y =  ( x - y)  ( x+ xy + y)

                  19.  x+ y+ z-xy - yz - zx = $\frac{1}{2}$ [( x - y)+ (y -z)+ ( z - x)2]  

Examples based on Identity:

                 Example 1:  Factorize the term  (xy)2 – 82

                 Solution:     Given (xy)2 – 82
                 Step 1: First check and make use of identity (a + b) (a - b) = a2 -b2              
                 Step 2: Assign the value in identity 
                                   ( xy )2 – 82    =  ( xy + 8 ) ( xy - 8 )

                Example 2:  Expand ( x - 2y)2
         
                Solution :
                Step 1: Make use of the identity       ( a -b )2  =  a- 2ab + b2
                Step 2: Assign the value in equation  a = x, b = 2y   =  ( x)- 2 * x * 2y + (2y)2
                Step 3:   Simplify    =  x- 4xy + 4y2